Teacher training for bilingual education of deaf in child education and initial series of fundamental education - Cicilino, Joice Emanuele Munhoz (2018)
This theoretical work implied to analyze how the teacher training in the bilingual education of the deaf in early childhood education and initial grades of elementary education have been represented in the productions of relevant sources in the Brazilian academic and scientific scenario between 2005 and 2015, a period related to the designations of Decree no. 5626 / 2005. The conclusion is that, although studies on teacher training for bilingual education of the deaf have contributed important reflections, the subject is not sufficiently explored in the scientific literature. Little headway has been made in the Brazilian scenario, regarding the teacher training to work with deaf students in the bilingual perspective, as well as in the implantation of bilingual educational models for these students.